2014
DOI: 10.1183/09031936.00060214
|View full text |Cite
|
Sign up to set email alerts
|

Early exposure to bio-contaminants and asthma up to 10 years of age: results of the HITEA study

Abstract: Inverse associations have been found between exposure to bio-contaminants and asthma and allergies. The aim of this study was to prospectively assess whether early exposure to bio-contaminants in dust is associated with asthma and allergy later in childhood among children from (sub)-urban areas.In subsets of three European birth cohorts (PIAMA: n=553; INMA: n=481; and LISAplus: n=395), endotoxin, (1,3,)-β-D-glucan and extracellular polysaccharide were measured in dust from living rooms shortly after birth. Cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In addition, the long‐term implications of these results are not clear. The association between early‐life exposure to microbial markers (endotoxin, EPS, or β‐glucan) and asthma up to the age of 10 years has been investigated in INMA, a subsample of LISAplus participants, and in the PIAMA intervention study participants . Like for the exposure to allergens reported in our study, no significant associations were observed between early‐life exposure to high concentrations of microbial markers and asthma.…”
Section: Discussionmentioning
confidence: 55%
“…In addition, the long‐term implications of these results are not clear. The association between early‐life exposure to microbial markers (endotoxin, EPS, or β‐glucan) and asthma up to the age of 10 years has been investigated in INMA, a subsample of LISAplus participants, and in the PIAMA intervention study participants . Like for the exposure to allergens reported in our study, no significant associations were observed between early‐life exposure to high concentrations of microbial markers and asthma.…”
Section: Discussionmentioning
confidence: 55%
“…2 Accordingly, intimate exposure to environments rich in microbes, such as those associated with traditional farming practices, might decrease the risk of asthma and other allergic diseases. 3 Earlier epidemiologic studies on home microbial exposure and asthma were based on characterization of exposure through measures of general microbial markers, [4][5][6][7] such as endotoxin in dust samples (reviewed by Doreswamy and Peden 8 ). We have previously shown in this cohort that the quantity of exposure to bacterial and fungal cell-wall components in early life has a bell-shaped association with asthma at the age of 6 years.…”
Section: Abbreviations Usedmentioning
confidence: 99%
“…Another limitation is that asthma status was assessed from questionnaires and not based on lung function tests. However, the questionnaire-based outcome is used in large birth cohort studies 54,55 and it offers data for many subjects, while lung function measurements are more costly and therefore often not feasible for all participants.…”
Section: Strengths and Limitationsmentioning
confidence: 99%